2009
DOI: 10.1097/mlr.0b013e31819432a0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Integrated HIV Care on Patient Health Outcomes

Abstract: Background Control of viral replication through combination antiretroviral therapy (cART) improves patient health outcomes. Yet many HIV-infected patients have co-morbidities that pose social and clinical barriers to achieving viral suppression. Integration of subspecialty services into HIV primary care may overcome such barriers. Objective Evaluate effect of Integrated HIV Care on suppression of HIV replication. Research Design A retrospective cohort study of HIV patients from five Veterans Affairs health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 42 publications
0
51
0
1
Order By: Relevance
“…The link between mental health, substance use, and clinical progression of HIV disease is also wellestablished (Hoang et al, 2009). Thus, provision of these services should not be considered an adjunct to medical care but a necessary component of care for those who need these services.…”
Section: Discussionmentioning
confidence: 99%
“…The link between mental health, substance use, and clinical progression of HIV disease is also wellestablished (Hoang et al, 2009). Thus, provision of these services should not be considered an adjunct to medical care but a necessary component of care for those who need these services.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women in FGs identified that because OAT participation required completion of annual medical exams, they were more likely to be tested for HIV and Hepatitis C, and to then be referred to specialized treatment centers. Integrated treatment for medical, psychiatric, and substance use disorders is an evidence-based effective strategy to improve care engagement along the HIV care continuum (Hoang et al, 2009; Soto, Bell, Pillen, Hiv/Aids Treatment Adherence, & Cost Study, 2004; Volkow & Montaner, 2011) and has been documented to improve numerous quality health indicators in Ukraine (Bachireddy et al, 2014). In the BHIVES multisite demonstration project of integrated buprenorphine and HIV care, those retained on buprenorphine at 6 months were significantly more likely to be retained in HIV care, prescribed ART and achieve viral suppression (Altice et al, 2011).…”
Section: 1 Discussionmentioning
confidence: 99%
“…In South Africa, PLWHA integrated into general medical health systems with access to comprehensive social and mental health services were three times more likely to achieve HIV viral load suppression on ART and to show improved overall survival (South African STRETCH study protocol). 23,24 Chinese HCW are justifiably concerned for their safety due to inadequate local infection control protocols and post exposure prophylaxis practices; for example, nearly 75% of HCW across several studies from China reported occupational exposure to blood and bodily fluids. 21,25,26 A nationally funded cross-sectional study of a 900-bed academic teaching hospital in Beijing in [2003][2004] reports an incidence rate of 66.3 per 100 for blood and body fluid exposure, averaging out to 7.5 occupational exposures per HCW per year, mostly among surgical staff -a concerning revelation that requires urgent attention.…”
Section: Discussionmentioning
confidence: 99%